Foreign Experience Related to the Formation of Patriotic Values of Students of Higher Educational Institutions - Seitkasimov Janabay (Academicia Globe: Inderscience Research, 2025)
This article explores foreign experiences and best practices in the formation of patriotic values among students of higher educational institutions. Using a comparative and analytical approach, the study examines educational policies, ideological frameworks, and socio-cultural mechanisms applied in countries such as the United States, China, and Russia to strengthen national identity, civic responsibility, and social cohesion among youth. The research is based on the analysis of normative documents, academic literature, and educational practices related to civic and patriotic education. The findings demonstrate that effective patriotism education is achieved through curriculum integration, experiential learning, community engagement, digital platforms, and state-supported programs that emphasize moral values, historical awareness, and social responsibility. The study concludes that adapting international experience to national contexts can contribute to the development of a systematic and sustainable model of patriotic education in higher education institutions.